Anaesthetic management of liver transplantation in patients with fulminant hepatic failure - Naved, Saad Ahmed; Sadiq Shoukat Ali Parpia (Journal of the Pakistan Medical Association, 2024)
Acute Liver Failure (ALF) is associated with rapidly progressive multiorgan failure and may even lead to death. Although liver transplantation (LT) has emerged as the only viable treatment option, there are many challenges associated with LT. The literature available from developed countries mainly focuses on the prognosis of ALF with limited focus on the anaesthetic management of LT. In the developing world particularly, the facility and experience of LT is relatively new. This case report presents the first case from Pakistan regarding the anaesthesia management of ALF. It discusses the management of a 46-year-old female who underwent emergency LT which includes initiation of Total Intravenous Anaesthesia, steps to reduce intra-cranial pressure, continuous Renal Replacement Therapy, and correction of coagulopathy using thromboelastography. To conclude, a holistic understanding of pre, intra, and post-operative anaesthetic management of liver transplantation requires a multi-disciplinary team management and can significantly improve the survival rates. Keywords: Liver Transplant, Anaesthesia, Liver Failure.